1994
DOI: 10.1130/spe292-p191
|View full text |Cite
|
Sign up to set email alerts
|

Hosgri fault zone, offshore Santa Maria Basin, California

Abstract: The Hosgri fault zone (HFZ) Is the name given to the southern section of the major coastal fault in central California. The Hosgri separates Transverse Range structure from offshore Santa Maria Basin structure and is a key element for any tectonic model that includes this economically significant region. Previous published maps have not adequately defined the southern termination of the HFZ, the style of faulting on the HFZ, and the relation of the HFZ to surrounding structures. Using more than 1,500 mi of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…1;Hanson et al, 2004;Lettis et al, 2004;Dickinson et al, 2005). At its south end, the Hosgri fault initiates at the northern boundary of the western Transverse Range province offshore Point Arguello (Steritz and Luyendyk, 1994;Sorlien et al, 1999). As it extends north, this mainly offshore fault system intersects the Big Sur coast at Piedras Blancas and at Point Sur where strands are referred to as the San Simeon and Sur faults.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…1;Hanson et al, 2004;Lettis et al, 2004;Dickinson et al, 2005). At its south end, the Hosgri fault initiates at the northern boundary of the western Transverse Range province offshore Point Arguello (Steritz and Luyendyk, 1994;Sorlien et al, 1999). As it extends north, this mainly offshore fault system intersects the Big Sur coast at Piedras Blancas and at Point Sur where strands are referred to as the San Simeon and Sur faults.…”
Section: Introductionmentioning
confidence: 92%
“…Where the faults overlap, the transfer of slip (i.e., stepover) results in the development of a rhomboidal pullapart basin (DiSilvestro et al, 1990;Hanson et al, 2004). The width of the stepover (~5 km) is considered too large for a transfer of slip during a large earthquake, so the maximum rupture length for an earthquake along the Hosgri fault zone is the distance between a Hosgri endpoint northwest of Point Estero and the southern termination of the fault offshore Point Arguello (Steritz and Luyendyk, 1994;Lettis et al, 2004), ~110 km.…”
Section: Fault Location and Lengthmentioning
confidence: 99%
“…Offset along the H-SS segment of the H-SS-SG fault zone that is less than the offset to the north of SS (see other segments discussed below) and south of Point Arguello (PA, Figure 1) is either owing to: (i) strike-slip being taken up in thrust faulting and folding at the southern end of the Hosgri segment (Steritz and Luyendyk 1994;Sorlien et al 1999aSorlien et al , 1999b, (ii) crustal shortening within the rotating Transverse Ranges (Dickinson et al 2005), (iii) slip along yet-to-be-identified faults in the offshore or Santa Maria basin, also ruling out crustal shortening Langenheim et al 2010), (iv) ∼15 km (9 mi) of slip inland from near Point Buchon and the Diablo Canyon nuclear reactor along the onshore OWHF zoneOWHF , or (v) 23 km (14 mi) of dextral slip on the OWHF zone ) (OWHF, Figure 1). …”
Section: Dextral Slip On the Northern San Andreas-pilarcitossan Gregomentioning
confidence: 99%
“…The Hosgri-San Gregorio fault system, the most extensive of these western structures, extends about 400 km along the central California coast. At its south end, the Hosgri fault initiates at the northern boundary of the western Transverse Range Province offshore Point Arguello and Point Conception (Steritz and Luyendyk, 1994;Sorlien et al, 1999). As it extends north, this mainly offshore fault system intersects the Big Sur coast at Piedras Blancas and at Point Sur, where strands have been referred to as the San Simeon and Sur faults (Dickinson et al, 2005).…”
Section: Introductionmentioning
confidence: 97%